The effect of mechanical activation of nitinol powder on the interaction with hydrogen; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Abdulmenova E. V. Ekaterina Vladimirovna (2019, 2019)
Title screen